The role of AGN feedback in the baryon cycle at z ∼ 2. Issue Volume 15:Issue S359(2020) (March 2019) - Mainieri, Vincenzo
Abstract: In this proceeding I will summarize our on-going observational campaign to characterize Active Galactic Nuclei (AGN) driven ionized gas outflows at z ˜ 2 and assess their impact on galaxy evolution. The results are mostly derived from a recently completed SINFONI/VLT Large Programme named SUPER, conducted with Adaptive Optics to reach a spatial resolution of ˜2 kpc at z ˜ 2.